What boxing-related stimuli reveal about response behaviour - Ottoboni, G.; Russo, G.; Tessari, A. (Journal of Sports Sciences, 2015)
When two athletes meet inside the ropes of the boxing ring to fight, their cognitive systems have to respond as quickly as possible to a manifold of stimuli to assure victory. In the present work, we studied the pre-attentive mechanisms, which form the basis of an athlete`s ability in reacting to an opponent`s punches. Expert boxers, beginner boxers and people with no experience of boxing performed a Simon-like task where they judged the colour of the boxing gloves worn by athletes in attack postures by pressing two lateralised keys. Although participants were not instructed to pay attention to the direction of the punches, beginner boxers` responses resembled a defence-related pattern, expert boxers` resembled counterattacks, whereas non-athletes` responses were not influenced by the unrelated task information. Results are discussed in the light of an expertise-related action simulation account.